Genes and Sales - Gong, Shiyang; Li, Qian; Su, Song; Zhang, Juanjuan (Management Science, 2024)
This paper presents one of the first marketing applications of molecular genetics. We report evidence that salespeople’s genetic variants linked to educational attainment predict sales performance. Both genetics and selling effort contribute to sales performance, whereas genetics contribute more than personality traits. We further show that adaptive learning, as captured in salespeople’s customer orientation and opportunity recognition skills, may explain the gene-sales relationship. We discuss the implications of these findings for sales management and the value of genetic research for the marketing field. This paper was accepted by Matthew Shum, marketing. Funding: S. Gong acknowledges financial support from the NSFC [Grant 71972040] and Fundamental Research Funds for the Central Universities [2022NTSS43]. Q. Li acknowledges financial support from the NSFC [Grant 72072014] and Young Talent Program of Beijing Foreign Studies University. S. Su acknowledges financial support from the NSFC [Grant 71872016]. Supplemental Material: The data files and online appendix are available at https://doi.org/10.1287/mnsc.2023.4879 .